2017
DOI: 10.1159/000476026
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Pulmonary Langerhans Cell Sarcoma Simultaneously Diagnosed with Cutaneous Langerhans Cell Histiocytosis Studied by Whole-Exome Sequencing

Abstract: Langerhans cell histiocytosis (LCH) and Langerhans cell sarcoma (LCS) are clonal proliferations of Langerhans-type cells. Unlike in LCH, the pathophysiology and clinical course of LCS are unclear due to its rarity. Here, we report the case of a 73-year-old male patient who was diagnosed with cutaneous LCH and pulmonary LCS at the same time. Pathological review of these 2 tumors revealed similar immunohistochemical findings. However, the tumor cells in LCS had more aggressive cytological features than those in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…The efforts by Karai et al have been beneficial in providing an insight that mutations within the TP53 gene can also be associated with LCS [52]. This finding was also further supported within the case report published by Kim et al, which also discussed on the presence of TP53 mutations in LCS as well as presenting us with a whole exonome analysis of LCS [12]. A further report published by Katsuragawa et al, also discussed about TP53 mutations and its presence within LCS; this report also discussed about CDKN2A deletion, which has rarely been seen within LCS [53].…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…The efforts by Karai et al have been beneficial in providing an insight that mutations within the TP53 gene can also be associated with LCS [52]. This finding was also further supported within the case report published by Kim et al, which also discussed on the presence of TP53 mutations in LCS as well as presenting us with a whole exonome analysis of LCS [12]. A further report published by Katsuragawa et al, also discussed about TP53 mutations and its presence within LCS; this report also discussed about CDKN2A deletion, which has rarely been seen within LCS [53].…”
Section: Discussionmentioning
confidence: 59%
“…It is also important to mention that LCS should not be confused with langerhans cell histiocytosis (LCH), which has a shared cellular origin to that of LCS. Although having identical lineage, LCH and LCS morphology differs from one another with LCH having monoclonal proliferation and having benign course while LCS has been observed to have more malignant features and an unfavorable prognosis [12,13]. It is widely accepted that LCH, which presents with increased numbers of atypical tumor cells should be considered as LCS and be regarded as a separate entity [2,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Kim et al, has discovered the stop-gain mutation in TP53 gene in Langerhans cell sarcoma through WES. Both the NGS and ES identified promoter, coding and non-coding variations in maximum all the diseases/disorders [17]. Several studies have confirmed both the NGS and ES has high successful rate in the clinical and medical genetics.…”
Section: Introductionmentioning
confidence: 84%
“…A literature searched revealed ten English‐language papers reporting genetic alterations in LCS 3–8,10–13 . Six case reports, 3–8 three of which included WES data, 4–6 indicated causative alterations such as mutations related to activation of the MAPK pathway ( BRAF , KRAS , MAPK2A1 or NRAS ), homozygous deletions of CDKN2A/(2B) , and/or a loss‐of‐function mutation of TP53 (Table 1). The present case also exhibited CDKN2A deletion and a pathogenic missense mutation in TP53 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…However, the underlying molecular features of LCS that could explain its aggressive behavior or pathogenesis, and lead to the development of more effective treatment strategies, are poorly understood, except for the reported presence of a few genetic alterations, such as mutations of MAPK‐related genes, CDKN2A or TP53 3–8 …”
Section: Introductionmentioning
confidence: 99%